INTIMATE PARTNER VIOLENCE AND INCIDENCE OF HYPERTENSION IN WOMEN - Mason, SM (2012)
PURPOSE: Intimate partner violence, a prevalent stressor for women, may influence cardiovascular disease risk. We estimated the association between intimate partner violence and development of hypertension, an important risk factor for cardiovascular disease, using data on intimate partner violence in the Nurses’ Health Study II cohort. METHODS: Intimate partner violence measures included adult lifetime physical and sexual partner violence and the Women’s Experiences with Battering Scale, which ascertained women’s subjective experience of recent emotional abuse. Physician-diagnosed hypertension was self-reported on biennial questionnaires. We used Cox proportional hazards models to estimate the association between report of intimate partner violence in 2001 and incidence of hypertension from 2001 through 2007. RESULTS: Of 51,434 included respondents, 22% reported being physically hurt and 10% reported being forced into sexual activities at some point in adulthood by an intimate partner. After adjustment for confounders, physical and sexual abuse were not associated with hypertension. However, women reporting the most severe emotional abuse had a 24% increased rate of hypertension (hazard ratio=1.24; 95% confidence interval: 1.02, 1.53) when compared to women unexposed to emotional abuse. CONCLUSION: Hypertension risk appears to be elevated in the small number of women recently exposed to severe emotional abuse.